Human capital systems, analytics, and data mining - Hughes, Robert Clayton (Chapman & Hall/CRC data mining & knowledge discovery series ;, 2019)
"This book fills a void in the systems and big data space with regard to human capital systems, data architecture, analytics, and systems. It is designed both as a text for graduate level courses in human resource systems, human capital analytics, and data mining as well as a resource for human capital analytical professionals in the course of ongoing contemporary research in all functional areas of human capital, including compensation, benefits, talent acquisition, and performance"--